Socialand tourism: concept formation - Vorvul, Ju. V.; Pererva, P. G. (My University, 2023)
The report substantiates that social tourism is aimed at the category of people with a low standard of living, financing is most often carried out at the expense of taxpayers and is subsidized by the state. At the same time, the main idea is to make tourist services available to the public. This requires a clear scheme for identifying the financial capabilities of each individual citizen and providing targeted assistance.
Соціальний туризм: формування концепції
Keywords: demand; development prospects; social tourism; supply